Mean Platelet Volume Decreases in Adult Patients With Obstructive Sleep Apnea After Uvulopalatal Flap Surgery. Issue 7 (October 2015) - Simsek, Gokce; Haytoglu, Suheyl; Muluk, Nuray Bayar; Arikan, Osman Kursat; Cortuk, Mustafa; Kiraz, Kemal
Abstract : Aim: The main purpose of the study was to investigate changes in mean platelet volume (MPV) values in patients with obstructive sleep apnea syndrome (OSAS) who had undergone uvulopalatal flap (UPF) surgery. Method: The study included a review of the medical records of 37 adult patients who had undergone UPF surgery after being diagnosed with OSAS. The baseline blood parameters of patients, including the MPV and platelet distribution width (PDW) values, were measured and repeated 3 months after treatment. Polysomnographic evaluations of the patients were also performed during admission and the 3rd month control. Comparisons of MPV values and their correlation with polysomnographic parameters were the main outcomes measured. Results: The blood parameters of all patients were similar except for MPV values, which were significantly lower after treatment ( P  < 0.001). Patients' apnea hypopnea index (AHI) and apnea episodes were significantly reduced after the UPF surgery, whereas their oxygen saturation significantly increased ( P  < 0.001). The MPV values were not correlated with polysomnographic parameters ( P  > 0.05). Conclusion: The UPF surgery, which is a relatively simple surgical intervention to treat OSAS, alleviates nocturnal hypoxic episodes and lowers platelet volume. These may both be important predictors of adverse cardiovascular outcomes related to OSAS.